FASILITAS SANITASI PADA WISATA RELIGI SUNAN AMPEL SURABAYA TAHUN 2016 - Ennovika Egatha Mareta; Bambang Sunarko; Suprijandani . (GEMA LINGKUNGAN KESEHATAN, 2016)
Tourism is a gathering place for a lot of people both adults and children so that it potential both as the site of disease transmission, environmental pollution, or other health problems. Therefore, the facilities provided must be complete, so that surveillance and inspection of sanitation in public places is very necessary to prevent transmission of disease and other health problems as well. This research was descriptive, which will describe about the state of sanitation facilities in SunanAmpel Religious Tourism of Surabaya Year 2016. Data collection was conducted by interviewing the manager and observation by using the tourism object appraisal form. Based on the results of observation at the sites, the object was concidered fair in category (69.7%). This case due to the state of the environment also in fair category (73%), the state of sanitation facilities was fair category (77%), state of the supporting facilities down to poor category (35%), the state of mosque sanitation included in the good category (82%). Final result of study concluded that the state of Sunan Ampel Religious Tourism of Surabaya was in the category of Fair (69.7%); it is suggested to the manager of the Sunan Ampel Religious Tourism of Surabaya to continuously monitor and keeping clean the environment of mosque area, grave, and the cleanliness of toilets. The trash place should be replaced using the garbage bins which are not easily corroded and fitted with a lid, janitors expected to make a schedule of transporting waste to landfill in maximum of every 3 days and move poolling locations to other empty sites. In the tourism object it’s suggested to provide health tools/facilities, with the availability of First Aid box. Keywords : Sanitation Facilities, Sunan Ampel Religious Tourism of Surabaya